A Rietveld refinement method for angular‐ and wavelength‐dispersive neutron time‐of‐flight powder diffraction data. (3rd December 2015) - Jacobs, Philipp; Houben, Andreas; Schweika, Werner; Tchougréeff, Andrei L.; Dronskowski, Richard
Abstract : This paper introduces a two‐dimensional extension of the well established Rietveld refinement method for modeling neutron time‐of‐flight powder diffraction data. The novel approach takes into account the variation of two parameters, diffraction angle 2θ and wavelength λ, to optimally adapt to the varying resolution function in diffraction experiments. By doing so, the refinement against angular‐ and wavelength‐dispersive data gets rid of common data‐reduction steps and also avoids the loss of high‐resolution information typically introduced by integration. In a case study using a numerically simulated diffraction pattern of Rh0.81 Fe3.19 N taking into account the layout of the future POWTEX instrument, the profile function as parameterized in 2θ and λ is extracted. As a proof‐of‐concept, the resulting instrument parameterization is then utilized to perform a typical refinement of the angular‐ and wavelength‐dispersive diffraction pattern of CuNCN, yielding excellent residuals within feasible computational efforts. Another proof‐of‐concept is carried out by applying the same approach to a real neutron diffraction data set of CuNCN obtained from the POWGEN instrument at the Spallation Neutron Source in Oak Ridge. The paper highlights the general importance of the novel approach for data analysis at neutron time‐of‐flight diffractometers and its possible inclusion within existing Rietveld software packages.